The regional dimension of knowledge transfers: a behavioral approach - Tom Broekel; Martin Binder (Max Planck Institute of Economics, 2006)
Innovations are inherently connected to knowledge transfers. The need of face-to-face contacts to transfer tacit knowledge is commonly argued to cause a regional dimension of innovative activities. The paper presents an alternative explanation based on a model of boundedly rational actors who search for knowledge. It is shown that a regional dimension exists in these processes that results from a regional bias in an actor's search activities. Social embeddedness, a shared regional identity and limited spatial mobility foster this bias. We argue that insights from research on these topics can help to define the geographic size of a region.
Keywords: D83; O31; R12; B52; 330; Regional Economics; Innovation; Knowledge Transfers; Tacit Knowledge; Bounded Rationality; Wissenstransfer; Regionalökonomik; Raumwirtschaftstheorie; Beschränkte Rationalität